GAMBARAN STRATEGI COPING PADA SINGLE PARENT YANG BERCERAI KARENA PERSELINGKUHAN PASANGAN - Syifa Shabirah Amatullah; Rachmawati, Rachmawati (Psychology Journal of Mental Health, 2019)
Abstract. This study aimed to find out what coping strategies are used to survive and faced the problems and how the ability of single parents to rise after divorce. This study used qualitative research method. Researchers used purposive sampling techniques to determine sbubject. Subjects in this study are single parent who divorced due to ex-husband cheating. The main subjects in this study were 2 people. There were also 2 secondary subject had same characteristics with the main subject. The data obtained are analyzed and interpreted using Moutakas theory through epoche, reduction, imaginative variation, and also synthesis of meaning and essence. The results of this study indicate that coping strategies used by single parent to survive and faced problems are problem-focused coping, emotional-focused coping, hope for self-efficacy and social support. In addition, single parent also has resilience ability so that make them rise from deterioration after divorce.